2012
DOI: 10.1128/aac.06017-11
|View full text |Cite
|
Sign up to set email alerts
|

Potent Synergistic Effect of Doxycycline with Fluconazole against Candida albicans Is Mediated by Interference with Iron Homeostasis

Abstract: Doxycycline was found to act synergistically with the antifungal fluconazole against Candida albicans. Combination with doxycycline converts fluconazole from fungistatic to fungicidal, prevents the onset of drug resistance, and is also effective against a clinical isolate characterized by elevated resistance to fluconazole. Investigation of the interactions between the two drugs by way of checkerboard assays indicated that doxycycline had an influence on the MIC for fluconazole, as defined by CLSI standards, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 64 publications
3
122
1
Order By: Relevance
“…Fluconazole, the primary antifungal used to treat candidiasis, is fungistatic: it inhibits fungal growth but does not kill the majority of the cells. Combination therapies, in which a second drug is used together with fluconazole, have been reported to increase the potential therapeutic efficacy of fluconazole (Liu et al, 2014, Butts & Krysan, 2012Butts et al, 2013;Fiori & Van Dijck, 2012;Liu et al, 2014;Zeidler et al, 2013, and references within). However, the degree to which these different agents influence tolerance rather than resistance is usually not determined in a manner that permits quantitative comparison between different drug combination therapy regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Fluconazole, the primary antifungal used to treat candidiasis, is fungistatic: it inhibits fungal growth but does not kill the majority of the cells. Combination therapies, in which a second drug is used together with fluconazole, have been reported to increase the potential therapeutic efficacy of fluconazole (Liu et al, 2014, Butts & Krysan, 2012Butts et al, 2013;Fiori & Van Dijck, 2012;Liu et al, 2014;Zeidler et al, 2013, and references within). However, the degree to which these different agents influence tolerance rather than resistance is usually not determined in a manner that permits quantitative comparison between different drug combination therapy regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies demonstrated the in vitro synergisms between amphotericin B or fluconazole with azithromycin, clarithromycin, doxycycline, minocycline, or tetracycline against Aspergillus spp., Candida spp., and Fusarium spp. (18)(19)(20)(21)(22)(23), as well as other combinations of antibacterial and antifungal agents against pathogenic fungi, as reviewed by Afeltra and Verweij (24) and Liu et al (25).…”
mentioning
confidence: 99%
“…Fluconazole (FCZ) is most widely used to treat candidiasis infections because of its high bioavailability and low toxicity (11)(12)(13). However, excessive and indiscriminate clinical use of FCZ has led to the emergence of multiple-drug-resistant (MDR) strains of C. albicans (5,14,15).…”
mentioning
confidence: 99%